Research on Parametric Modeling and Model Transformation of Proton Hospital Based on BIM - Li, Shoufu; Yu, Tao; Liu, Yang; Li, Yan; Lei, Bo; Qiao, Wenjing; Zhang, Yuyan (Buildings (Basel), 2025)
Aiming at problems such as difficulty and low efficiency in modeling complex building structures in Revit and Abaqus, Revit and Dynamo visual programming modeling were used to realize rapid parametric modeling of structures, and a Revit–Abaqus model conversion interface was developed. Based on Revit’s API modeling function and Dynamo’s visual programming function, a proton hospital structure model was quickly created, secondary development of Revit conducted on Visual Studio 2022 using C# language, the Revit model exported to a single unified management .sat file, and a corresponding Python script file conforming to Abaqus generated. The script file contained all the .sat file path and parameter information to realize the conversion of the BIM model to Abaqus 2020 finite element software. The proposed modeling method can effectively expand the application range of BIM in a proton hospital project and effectively improve the efficiency of BIM modeling technology. The Revit–Abaqus model conversion interface developed can realize the automatic conversion of a BIM model to a structural analysis model. Compared with the traditional finite element modeling method, this effectively improves the modeling efficiency of structural analysis of proton hospital engineering and makes up for the shortcomings of BIM technology in structural analysis of proton hospital construction.